Determinan Rasio Keuangan dan Good Corporate Governance di Badan Usaha Milik Negara - Lucky Monic Sabatini; Siwi Nugraheni (Owner : Riset dan Jurnal Akuntansi, 2022)
The study is classification as a quantitative study intended to see if there is any impact between a financial ratio and good corporate governance on the profitability of State-Owned Enterprises. A total of 14 State-Owned Enterprises were used as research samples from 2016-2020. Microsoft Excel 2007 and E-views 9 were used to process data using regression data analysis methods that panel as an analysis technique and used by the 5% level. Research has shown that profitability has been significantly influenced by liquidity and the board of directors, while profitability has been not significantly influenced by leverage, independent commissioners, and auditing committees. Keywords: Financial Ratio, Good Corporate Governance, State-Owned Enterprises